La Chute d’Icare des Musées royaux des Beaux-Arts de Belgique réattribuée par l'examen de laboratoire - Léopold Kockaert (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The controversy about the attribution of « The Fall of Icarus» at the Brussels Museum of Fine Arts has been heightened many times, namely by a radiocarbon dating of the first canvas, from which it is concluded that P. Bruegel the Elder cannot have painted this canvas ; and more recently by the publication of a book by D. Allart and C. Curri, as well as a paper from these authors published in this Journal. It seems to me that the desattribution of this painting is not compatible with some results of  scientific examination that were  previously published in the literature. Therefore, I propose  to review the different studies about this painting in order to draw a conclusion that takes all of them into account. In particular, taking into account the analysis of a paint sample, I will provide an interpretation of the reflectograms of the underlying drawing that takes into account a probable transposition. I will finally demonstrate how different analyses lead to the conclusion that ``The Fall of Icarus´´ at the Royal Museum of Fine Arts is probably an authentic pannel by P. Bruegel, Father or Son, that has been heavily altered by a transposition on canvas.